Fatores determinantes na decisão de compra em posto de combustíveis: um estudo em Sobral-CE - Lima, Conceição Mirlete Vasconcelos (2007)
The present work was developed with the objective of analyzing the factors that influence the consumers’ behavior in their decision when buying fuel in gas stations located around and in the city of Sobral, Ceará. This work is characterized, therefore, like an exploratory, descriptive and comparative study, and relies on a field and bibliographical research. The bibliographical research approached themes related to strategic marketing at retail focusing on: the definitions and the evolutions of retail, the consumer’s behavior in their processes of decision, and the factors that influence the consumers’ behavior in their steps of purchase decisions. The field research involved four hundred and two consumers. The strategy used to get the data collection was an structured interview. Like an analysis instrument of the collected data, it was used the SPSS program, version 10.0 and EXCEL. The methods of presentation and the analysis of data were done in six blocks: In the first block the periphery gas stations are presented; in the second block, the downtown gas stations are presented; in the third block, the highway gas stations are presented; and in the last one, a comparative analysis is done involving all blocks. The obtained results led us to conclude that the main factor which influence the consumers in their purchase decision for one of the three gas stations is the quality of the fuel. It was also possible to observe that in the highway gas stations the different kinds of price, the 24 hour service, lubrication, the quickness in the purchase process, the quality and the variety of products represent very important factors in the consumers’ purchase decision. In the downtown gas stations only the factors ‘washing and oil change’ represent importance in the consumers’ choice in their purchase process, while in the periphery gas stations the factors that most influence the consumers in their purchase decisions are the good conditions of payment, like sales on instalment, the appearance of the employees, and credibility. However, relevant statistic differences were not observed between these two factors: localization and service quality.